Harmonic Distortion Evaluation Generated by PWM Motor Drives in Electrical Industrial Systems - Vladimir Sousa; Hernán Hernández Herrera; Enrique C Quispe; Percy R Viego; Julio R Gómez (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This paper evaluates the harmonic distortion generated by PWM motor drives in an electrical industrial system of a wheat flour mill company. For this, a comparative study between two industrial circuits connected at the same point of common coupling (PCC) with similar characteristics of load and transformers is presented. The difference is that one circuit has PWM motor drives and the other does not have them. In the study, a practical method based on the statistical characterization of the total harmonic distortion of voltage (THDV) and current (THDI), individual voltage distortion (IVD), individual current distortion (ICD) and K-Factor is applied. As result, it was observed that PWM motor drives generated voltage harmonics mainly of fifth and seventh order with values that exceed limits established by standards in both circuits. With these values, the operation of elements such as capacitors, motors and transformers can be affected. In the work is also demonstrated that in the analysis of harmonics is necessary to consider various parameters and not only one.